Feasibility of intravenous vitamin C supplementation in allogeneic hematopoietic cell transplant recipients - Gary L. Simmons; Roy Sabo; Rehan Qayyum; May Aziz; Erika Martin; Robyn J. Bernard; Manjari Sriparna; Cody McIntire; Elizabeth Krieger; Donald F. Brophy; Ramesh Natarajan; Alpha Fowler III; et al. (eJHaem)
Abstract Introduction Intravenous vitamin C was administered following hematopoietic stem cell transplant to mitigate nonrelapse mortality (NRM) in a Phase II clinical trial. Methods Patients with advanced hematologic malignancies received IV vitamin C, 50 mg/kg/day, in three divided doses on days 1–14 after HSCT, followed by 500 mg bid oral until 6 months. Results All patients enrolled (55) were deficient in vitamin C at day 0 and had restoration to normal levels. Vitamin C recipients had a trend for lower nonrelapse mortality (NRM, 11% vs. 25%, p‐value = 0.07) compared with propensity score‐matched historical controls. A similar trend toward improved survival was observed (82% vs. 62% p = 0.06), with no attributable grade 3 and 4 toxicities to vitamin C. Conclusion In patients undergoing allogeneic HSCT, repletion of vitamin C is feasible and may reduce NRM and improve overall survival. Randomized trials in large uniform cohorts of patients are needed to confirm the utility of this easily available and inexpensive therapy.